Russian Voice in World Literature: Classics of the Crisis Age - Vadim V. Polonskiy (Два века русской классики)
By the end of the 19th century, Russian literature had gained world- leading status. This process was connected in particular, with the political realities generated by Russia’s defeat in the Crimean War (1853–1856), the Franco-Prussian War of 1870–1871 (as a result of which the role of the ideal Other in French cultural consciousness was transferred from Germany to Russia) and the birth of L’Entente on the outskirts of the First World War. In this context, the importance of E.-M. de Vogüé’s book “Russian Novel” (1886), which played the role of a cultural accompaniment to the political doctrine of creating the Franco-Russian alliance (1891–1892), should be assessed. The links between politics and literature were often paradoxical. Thus, the Crimean War, accompanied in the West by building an anti-Russian propaganda industry, simultaneously contributed to the rooting of Russophile tendencies in Western European literature. The article pays special attention to modelling the image of the Other on the example of N. M. Karamzin and F. M. Dostoevsky. It is concluded that for the world’s critical reception, Russian classics are often fundamentally “non-classical”: they are a phenomenon of a Modern type associated with the metaphysics of the rational paradigm crisis.